A clinical study of deep neck space infections - Karodpati, Nayanna; Kuradagi, Vinayak; Chavan, Paresh; Pawar, Rishikesh; Kakollu, Lakshmi Sravya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Deep neck space infections are usually due to excessive growth of normal flora, mostly of polymicrobial in origin. Patients present acutely with complaints of, throat and neck pain, raised body temperature. The clinical presentation depends on the deep neck space affected. Methods: Current study was carried out in 25 patients who were diagnosed to have various deep neck infections Results: It was observed that the maximum number of cases were seen in the age group of 31-40 at 28%, followed by 21-30 age group at 20%, 16% each between 41-50 years and above 60 years. The male to female ratio is 1:0.78. The most common presenting complaints included fever (24 patients; 96%) and dysphagia (18 patients; 72%). 13 patients (52%) had associated systemic disease, 5 patients (20%) had history of diabetes mellitus and were on irregular treatment, 4 patients (16%) was on treatment for hypertensive. The most common infection was Ludwig’s angina seen in 13 patients (52%), followed by peritonsillar abscess 4 patients (16%). Out of 25 patients, 20 (80%) cases were treated successfully by incision and drainage. No growth was observed in 32% of the patients. Conclusions: Early diagnosis of deep neck space infection based on symptoms in susceptible patients is advisable to prevent complications and early recovery.